2007
DOI: 10.9752/ms025.03-2007
|View full text |Cite
|
Sign up to set email alerts
|

Delivering the Goods: Lessons Learned from Direct Delivery of Kentucky Catfish

Abstract: The U.S. Department of Agriculture (USDA) prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or part of an individual's income is derived from any public assistance program (Not all prohibited bases apply to all programs.) Persons with disabilities who require alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the benefits of using a 3PL provider do not always outweigh the costs. The Purchase Area Aquaculture Cooperative originally used a 3PL provider to handle distribution but found that the numerous fees charged by their provider were too expensive [127]. Additionally, using a 3PL resulted in longer delivery times, because the products were routed through a distribution center, rather than being delivered directly to customers.…”
Section: Third-party Logistics (3pl)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the benefits of using a 3PL provider do not always outweigh the costs. The Purchase Area Aquaculture Cooperative originally used a 3PL provider to handle distribution but found that the numerous fees charged by their provider were too expensive [127]. Additionally, using a 3PL resulted in longer delivery times, because the products were routed through a distribution center, rather than being delivered directly to customers.…”
Section: Third-party Logistics (3pl)mentioning
confidence: 99%
“…The Purchase Area Aquaculture Cooperative, a farmer cooperative in Kentucky, also uses different types of vehicles for different kinds of deliveries. Their system uses a leased truck to make small deliveries directly to customers, and distributors are hired to handle large deliveries [127]. Some RFSCs have also increased vehicle utilization through distribution network design.…”
Section: Efficient Vehicle Utilizationmentioning
confidence: 99%
See 1 more Smart Citation